THE INFLUENCE OF ONLINE SERVICES AND PROMOTIONS TO PURCHASHING DECISION OF ECONOMIC RAILWAY TRANSPORTATION IN SUMATERA SELATAN - Mujari Mujari (Unitri Press, 2017)
PT. Kereta Api Indonesia (Persero) or later called PT. KAI is one of transportation company which provide railway transport services in order to facilitate the displacement people and goods. PT KAI use internet technology to provide online ticketing system. This innovation with online system must be supported by good promotion to increase the purchasing decicion of railway transportation. This studi aims to determine the effect of online services and promotions to purchasing decicion of economic railway transportation in Sumatera Selatan. This study uses asosiatif research method with questionnaire. Samples are 100 passengers chosen by accidental sampling technique. The analysis used is multiple linier regression. The result shows that online system did not influence the purchashing decicion of railwal ticket, hence promotion did influence the purchasing decicion. Based on the result, the main reason of purchasing railway ticket in Sumatera Selatan are a word of mouth and formal promotions. To increase the custumer numbers, PT. KAI must give better innovation on online system so they can compete in the market.